Revealing ancient gold parting with silver and copper isotopes: implications from cementation experiments and for the analysis of gold artefacts - Berger, Daniel; Brauns, Michael; Brügmann, Gerhard; Pernicka, Ernst; Lockhoff, Nicole (Archaeological and anthropological sciences, 2021)
Gold parting enabled the production of very pure gold for various purposes from the sixth century BC onwards, but analytical proof of this pyrotechnical process is difficult. We describe a new analytical approach for the identification of purified gold combining silver and copper isotopic with trace element analyses. Parting experiments were performed with gold-silver-copper alloys using the classical salt cementation process to investigate potential silver and copper isotope fractionation and changes in trace element concentrations. In addition, we provide the first comprehensive dataset of silver isotope ratios of archaeological gold objects from the Mediterranean and Central Europe to test whether or not gold refining can be identified on the basis of isotope systematics. The results show that very heavy silver and copper isotopic compositions are clear evidence for parted gold, but that the application of copper isotopes might be limited.
Gesehen am 09.06.2023